O fenômeno da evasão no ensino superior no curso de administração no Estado do Rio de Janeiro nos anos de 2006 a 2012: um estudo de caso UNIGRANRIO - Lourenço, Ana Vicentina Marçal (2014)
The core of this study is to analyze the phenomenon of evasion in the course of management, adding at perspective of the student, seeking to identify and to classify the main reasons and establish a critical profile of groups of students that because were framed in specific kinds or circumstances would be more vulnerable to abandon his studies. In the future, this could be the input to build predictive models for the prevention of evasion and adaptation of strategies to combat evasion in educational institutions. It is based on a case study in a private university in the state of Rio de Janeiro in municipality of Duque de Caxias, the Unigranrio, with students administration of business that dropout in the period 2006-2012. Using interviews and questionnaires focused to these students and analysis of the historical basis of academic data allowed identifying some groups and most critical situations for evasion, such student’s phase 1, especially in the first weeks of class, aged between 19 and 25 who live or work far from campus, with economic difficulties, and pregnant women. Further examined whether the key strategies and actions developed by Unigranrio, with intend to reduce student´s dropout: increased capillarity, diffusion of distance education, encouraging the use of public funding and grants.